Positive real-time PCR in pneumococcal meningitis 12 hours after initiation of antibiotic therapy – case report - Cem Thunstedt; Carla Palleis; Johannes Wischmann; Suzette Heck; Konstantinos Dimitriadis; Matthias Klein (BMC Neurology, 2025)
Abstract Background Purulent meningitis poses a significant clinical challenge with high mortality. We present the case of a 54-year-old female transferred to our emergency department with suspected bacterial meningitis, later diagnosed as an Austrian syndrome. Case presentation The patient exhibited subacute somnolence, severe headache, nausea and fever. Initial antibiotic therapy was initiated without successful lumbar puncture. Upon arrival at our hospital, she presented with septic shock, meningism, and respiratory symptoms. Lumbar puncture revealed cloudy cerebrospinal fluid with elevated cell count, protein, and low glucose. While blood and CSF cultures remained negative, multiplex PCR for Streptococcus pneumoniae was positive even 10 h after beginning of effective antibiotic therapy. Subsequent echocardiogram revealed mitral valve endocarditis and the patient underwent valve replacement. Conclusion Altogether, bacterial meningitis presents with cardinal clinical signs only half of cases. Lumbar puncture remains crucial, and our patient’s CSF findings aligned with bacterial meningitis. Multiplex PCR aided in diagnosis, even after antibiotic treatment. The case highlights the importance of prompt lumbar puncture despite antibiotic pre-treatment. The patient’s Austrian syndrome, characterized by meningitis, endocarditis, and pneumonia, emphasizes the need for vigilance regarding skin lesions, early cerebral infarctions, and iritis. This case emphasizes the complexity of bacterial meningitis diagnosis and the utility of multiplex PCR, especially in prolonged antibiotic-treated patients. However, PCR cannot replace cultures when it comes to adapting therapy based on the antibiotic sensitivity of the causative pathogen. Awareness of Austrian syndrome’s diverse manifestations is crucial for timely recognition and appropriate management.